Margay also hide their spots: first records of melanistic Leopardus wiedii from Colombia and Costa Rica - José F. González-Maya; Andrés Arias-Alzate; Ramón Granados-Peña; Diego A. Gómez-Hoyos; Jan Schipper; Miguel Majarrés-Morrón; Gustavo Majarrés-Pinzón (Revista Mexicana de Biodiversidad)
Melanism has been commonly recorded in tropical felids, especially within the genus Leopardus. However, so far there are no reports of the existence of melanism in Leopardus wiedii. Herein, we present the first report of melanistic individuals of margays, obtained in Colombia and Costa Rica. The low frequency and scarcity of melanistic margay records along its distribution reflect that this is potentially not an ecological or adaptive advantage for the species, and likely the mutation is not established, or even follows a random frequency in the populations.